A INSERÇÃO DE ACADÊMICOS DA ÁREA DA SAÚDE NA COMISSÃO DE INTEGRAÇÃO ENSINO - Ribas, Cristiane; Sauter, Angela M. W.; Jesse, Margarete V.; Santos, Elton D. C. d.; Ubessi, Liamara D.; Righi, Liane B. (Salão do Conhecimento, 2013)
Resumo